(untitled) (Al-Qamar, 2024)
This research explores the judiciary role in recognition of fundamental human rights, preservation of their civility and protection of laws. Government goals will better achieve by the standards developed by the judiciary in making people life easier, specifically in a context of Islamic teachings. Interpretation upon the comprehensive literature review, this study explores the relationship between the Government and the people and the international community through developing standards and laws in perception of Islam. Addressing the research question, “What role judiciary play in betterment of human’s life and as a guardian of the Constitution through embryonic standards and laws in Islamic perspective?” the study approaches the qualitative and analytical methodology. Data is collected through research, observations and studies conducted in Islamic communities and by the other scholars. The findings underscore the duties of the State and the rights of human by drafting limitation, preventions and equitable decisions. It delves into Islamic teachings influencing equitable enforcement of law and solidification of Human rights. It is further concluded that the State is obliged to constitute equal rights of freedom, democracy, social justice, tolerance equality of status as enunciated by Islam to ensure peace and protection in the country. It is recommended further to foster Islamic norms and values in judicial constitutions and policy makers for optimal protection of human rights and stability of political system.